Validation of a poisson-distributed limiting dilution assay (LDA) for a rapid and accurate resolution of multiclonal infections in natural Trypanosoma cruzi populations (2013)
Trypanosoma cruzi is the causative agent of American trypanosomiasis, a complex zoonotic disease that affects more than 10 million people in the Americas. Strains of this parasite possess a significant amount of genetic variability and hence can be divided into at least six discrete typing units (DTUs). The life cycle of this protist suggests that multiclonal infections may emerge due to the likelihood of contact of triatomine insects with more than 100 mammal species. To date, there have been a few studies on but no consensus regarding standardised methodologies to identify multiclonal infections caused by this parasite. Hence, the aim of this study was to develop and validate a limiting dilution assay (LDA) to identify multiclonal infections in T. cruzi populations by comparing the feasibility and reliability of this method with the widely applied solid phase blood agar (SPBA) methodology. We cloned reference strains belonging to three independent genotypes (TcI, TcII, and TcIV) and mixed infections (TcI + TcII) using LDA and SPBA; the comparison was conducted by calculating the feasibility and reliability of the methods employed. Additionally, we implemented LDA in strains recently isolated from Homo sapiens, Rhodnius prolixus, Triatoma venosa, Panstrongylus geniculatus, Tamandua tetradactyla, Rattus rattus, Didelphis marsupialis and Dasypus novemcinctus, with the aim of resolving multiclonal infections using molecular characterization employing SL-IR (spliced leader intergenic region of mini-exon gene), the 24S? rDNA gene and microsatellite loci. The results reported herein demonstrate that LDA is an optimal methodology to distinguish T. cruzi subpopulations based on microsatellite markers by showing the absence of multiple peaks within a single locus. Conversely, SPBA showed patterns of multiple peaks within a single locus suggesting multiclonal events. The biological consequences of these results and the debate between multiclonality and aneuploidy are discussed.